m7G-Related DNA Damage Repair Genes are Potential Biomarkers for Predicting Prognosis and Immunotherapy Effectiveness in Colon Cancer Patients - Chen, Shuran; Dong, Rui; Li, Yan; Zheng, Ni; Peng, Guisen; Lu, Fei; Qiu, Quanwei; Wen, Hexin; Wang, Yitong; Wu, Huazhang; Liu, Mulin (Frontiers in Genetics, 2022)
Objective m7G is a post-transcriptional modification modality, however, limited research has been conducted on its role in colon cancer. The deficiency of DNA damage repair (DDR) is the basis for the development of colorectal cancer. This study aimed to explore whether m7G-related DDR genes may be used as biomarkers to predict the prognosis of colon cancer patients. Methods Patient was typed into two clusters using a non-negative matrix factorization (NMF) on m7G-related DDR genes expression data obtained from the TCGA database, and risk models were constructed using typed differential genes. The reliability of risk models was assessed using DCA curves, and a Nomogram. Meanwhile, The ROC and C-index curves were used to compare the predictive significance of the risk models constructed in this study with other studies in terms of patient prognosis. Finally, we examined the influence of risk models on patients' immunity microenvironment and response to immune therapy. Finally, we used a series of cellular experiments to validate the effect of model genes on the malignant progression of CRC cells. Results Twenty-eight m7G genes were obtained from the GSEA database. Multi-factorial Cox and Lasso regression analysis was performed and six m7G-related DDR genes were identified for use in constructing the risk model. The prognosis and grading and staging of tumour tissues were worse for patients in the high-risk group than for those in the low-risk group. Additionally, the immune microenvironment status of patients in the high- and low-risk groups differed, suggesting that patients in the low-risk group may be more sensitive to immunotherapy, particularly immune checkpoint inhibitors. Finally, we found that depletion of ATP2A1, one of the risk genes in our model, significantly reduced cell proliferation and metastasis of CRC cells. Conclusion The m7G-related DDR genes can be used as important markers for predicting patient prognosis and immunotherapy response. Our data suggest that ATP2A1 may promote the proliferation and migration of colon cancer cells. These findings may provide new therapeutic targets for the treatment of colon cancer.